Hubungan Tipe Kepribadian Dengan Kejadian Depresi Pada Lansia Di UPT PSLU Jombang – Pare Kediri - Nurhidayah Nurhidayah; Ismu Basuki; Endik mufidatul Fitriah (coba, 2016)
The depression is one of the form of disturbance that gave rise to natural feeling symptoms indicating the dysfunction ofaphek, emotion, the mind, and a common activity. The purpose of this research is to know relations with type personality scene depression in elderly at UPT PSLU Jombang Pare Kediri. The research design that is used is analytic the correlation with the kind of research cross sectional. The population research is all for the elderly are at UPT PSLU Jombang Pare Kediri selected from as many as 73 seniors taken using a technique simple random of sampling. Variable free is a type personality and variable bound is the incident depression. Adaption of the data carried out using a questionnaire and questionnaires. Data expressed in the scale of nominal and ordinal as will analyzed with a test of the spearman rank with alpha 0,05. The research result obtained the majority of respondents had a role with two categories of extroverted that is as much as 40 respondents (54,8%). Half of the respondents suffer from depression being level that is as many as 31 respondents (42,5%). Of the total 73 respondents and there is a relationship with type personality scene depression in elderly at UPT PSLU Jomabang Pare Kediri ( Phi with p value = 0,000 < 0.05 then Ho rejected). The conclusion of this research is there is a relationship with type personality scene depression in elderly at UPT PSLU Jombang Pare Kediri. For it expected an improvement in environmental adjustment to from type personality extroverted ongoing form through existing activities in UPT PSLU. Keywords : the type personality, the incident depression, the elderly